Coprescribing of opioids and high-risk medications in the USA: a cross-sectional study with data from national ambulatory and emergency department settings - Dio Kavalieratos; Mohammed K Ali; Kara Suvada; Anna Zimmer; Jesse Soodalter; Jimi S Malik (BMJ Open)
Objective Describe trends in opioid plus high-risk medication coprescribing in the USA.Design Analyses of serial, cross-sectional, nationally representative data of the National Ambulatory Medical Care Survey (NAMCS) over 2007–2016 and the National Hospital Ambulatory Medical Care Survey (NHAMCS) over 2007–2018.Setting US ambulatory (NAMCS) and emergency department (ED, NHAMCS) settings.Participants Patient visits in which the patient was 18 years and older with an opioid prescription in the NAMCS or NHAMCS databases.Primary and secondary outcome measures Frequency of opioid plus high-risk medication coprescribing.Results From a combined sample of 700 499 visits over 2007–2018, there were 105 720 visits (15.1%) where opioids were prescribed. n=31 825 were from NAMCS and n=73 895 were from NHAMCS. The mean prevalence of coprescription of opioids and high-risk medications for the combined NAMCS and NHAMCS sample was 18.4% in 2007, peaked at 33.2% in 2014 and declined to 23.8% in 2016. Compared with adults receiving opioid prescriptions alone, those coprescribed opioids and high-risk medications were older, more likely female, white and using private or Medicare insurance (p<0.0001).Conclusions Coprescribing is more common in ambulatory than ED settings and has been declining, yet one in four patient visits where opioids were prescribed resulted in coprescribed, high-risk medications in 2016. Efforts and research to help lower the rates of high-risk prescribing are needed.